2019
DOI: 10.1111/hex.12933
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve participation in health‐care decisions in non‐Western countries: A systematic review and narrative synthesis

Abstract: BackgroundPatients' participation in medical decision making is an important aspect of patient‐centred care. However, there is often uncertainty about its applicability and feasibility in non‐Western countries.ObjectiveTo provide an overview and assessment of interventions that aimed to improve patients' participation in decision making in non‐Western countries.MethodOvid Medline, Embase, Cochrane Central Register of Controlled Trials, CINAHL, Ovid MEDLINE(R) Epub Ahead of Print, In‐Process, Other Non‐Indexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Third (aim 3), participants mentioned training (of both healthcare professionals and patients) and their motivation as facilitators to performing SDM, and their limited knowledge about SDM and lack of patient SDM education as barriers of practicing SDM in their clinical practice. These results are aligned with those of a recent systematic review on patient's involvement in decision-making in non-western countries that highlighted the need for healthcare professional and patient training in SDM [7]. Patients lack of familiarity with their rights and their low health literacy were acknowledged as barriers in other Iranian studies, as well [23,26].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Third (aim 3), participants mentioned training (of both healthcare professionals and patients) and their motivation as facilitators to performing SDM, and their limited knowledge about SDM and lack of patient SDM education as barriers of practicing SDM in their clinical practice. These results are aligned with those of a recent systematic review on patient's involvement in decision-making in non-western countries that highlighted the need for healthcare professional and patient training in SDM [7]. Patients lack of familiarity with their rights and their low health literacy were acknowledged as barriers in other Iranian studies, as well [23,26].…”
Section: Discussionsupporting
confidence: 81%
“…Healthcare professionals' implementation of SDM in their practice has been slow [4]. With respect to non-western countries, a systematic review showed that patient participation in decision making can be feasible and effective, provided healthcare professionals receive training [7]. However, very little training is provided.…”
Section: Introductionmentioning
confidence: 99%
“…These are fundamental to promote patient active participation in healthcare decisions. 55 Future research could focus on developing culturally appropriate decision aids among Arabic-speaking population and evaluating the impact of such tools on improving the extent of SDM. Additionally, to foster SDM in the country, in-depth exploration of physicians’ perspectives is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although beyond the scope of this project, our findings suggest that participants in Hong Kong and Philippines may see themselves as less active participants, perhaps lower status, where they are primarily given information by the doctor and are, hopefully, asked questions to contribute to the consultation. Dolan et al (2019) highlighted that communication skills training for patients and providers from countries where participation is less active can increase patient participation and involvement in health care decisions. However, even with coaching, Kim et al (2003) found that patients felt it was important that explicit permission or endorsement be given by providers for patients to speak up and ask questions.…”
Section: Discussionmentioning
confidence: 99%